Brain Research Using Computer Test. (2016) - Mikolajczyk, Tadeusz; Moldovan, Flaviu; Ciobanu, Ileana; Chalupczak, Agata; Marin, Andreea Georgiana
Abstract: Efficiency of learning largely depends on the proper transfer of knowledge and skill in taking notes. Experience shows that students' autonomy is mainly blocked in schools. Knowledge about the sensory modality and hemispheric lateralization helps students to better use the brain. The purpose of the study is to diagnose the preferences of the use of a specific brain hemisphere and to determine the sensory modality preferred by the brain for the students in engineering. The methodology of research consisted in data collection from 91 subjects, second year students, and processing by using the "Brain Works" software. This software uses graphical and text questions, calculates the brain hemispheric dominance and recognizes subject's preferred knowledge caption mode: visual or audio. The interpretation of the results provides an individual learning style description, concluding a clear tendency to use the left hemisphere, a superior domination of the use of the visual sense for learning and indication for the contestants to optimize their way of learning. The "Brain Works" also helped the subjects by enhancing the process of notes taking through skill training, fact that has a beneficial effect on faster and more effective learning and provides an important cognitive training tool for cognitive rehabilitation.